2-[(E)-2-(4-Methylbenzenesulfonamido)ethyliminiomethyl]-4-nitrophenolate - Marife Tüfekçi; Gökhan Alpaslan; Mustafa Macit; Ahmet Erdönmez (Acta Crystallographica Section E, 2009)
The molecule of the title compound, C16H17N3O5S, crystallizes in a zwitterionic form, with a strong intramolecular N—H...O hydrogen bond. The dihedral angle between the two benzene rings is 7.06 (9)°. In the crystal, molecules are linked into chains along the c axis by intermolecular N—H...O hydrogen bonds.